1983
DOI: 10.1111/j.1365-2265.1983.tb03215.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preoperative and Postoperative Acth Concentrations After Bilateral Adrenalectomy in Cushing's Disease

Abstract: Up to one-third of subjects who have had bilateral adrenalectomy for treatment of Cushing's disease will develop Nelson's syndrome. To examine the value of pre-operative ACTH assays in predicting outcome, we have studied fifteen cases of Cushing's disease treated by bilateral adrenalectomy and pituitary irradiation. Three patients developed Nelson's syndrome. There was no significant correlation between preoperative ACTH level, either 8 am 'basal' or during metyrapone testing, and ACTH concentration post-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 6 publications
2
33
2
2
Order By: Relevance
“…However, the evidence is not conclusive, and a correlation between urinary cortisol levels and the risk of subsequent development of Nelson's syndrome has not been demonstrated in some studies (13,30,32). Pre-operative urinary cortisol levels cannot therefore be advocated as a reliable predictive factor for the subsequent development of Nelson's syndrome.…”
Section: High Urinary Cortisolmentioning
confidence: 80%
See 2 more Smart Citations
“…However, the evidence is not conclusive, and a correlation between urinary cortisol levels and the risk of subsequent development of Nelson's syndrome has not been demonstrated in some studies (13,30,32). Pre-operative urinary cortisol levels cannot therefore be advocated as a reliable predictive factor for the subsequent development of Nelson's syndrome.…”
Section: High Urinary Cortisolmentioning
confidence: 80%
“…Suboptimal or absent steroid replacement therapy post TBA may increase the risk of developing Nelson's syndrome (41,42) or even result in transformation of a pre-existing adenoma into a more aggressive tumour subtype (3,26). However, most studies have not shown this (3,13,32).…”
Section: Insufficient Exogenous Steroid Replacement Therapy Post Tba mentioning
confidence: 88%
See 1 more Smart Citation
“…21 One of the best predictive factors for Nelson's syndrome is high levels of ACTH after adrenalectomy, but no definitive threshold value has been established. 5,18,33,34,51,55,66 A rapid rise of plasma ACTH levels in the first year after bilateral adrenalectomy seems to be a strong predictor because of its association with tumor progression.…”
Section: Predictive Factorsmentioning
confidence: 99%
“…No nosso serviço, devido ao pequeno número de casos submetidos a esse procedimento, não foi possível concluirmos quanto à existência de seu efeito protetor. Os dados existentes na literatura também não são conclusivos, alguns estudos indicando efeito benéfico (19)(20)(21) …”
Section: Síndrome De Nelsonunclassified